HUBUNGAN ANTARA EMOTION FOCUSED-COPING DENGAN PSYCHOLOGICAL WELL-BEING PADA GURU SMK SWASTA - Dewanti Indah Permatasari; Doddy Hendro Wibowo (Media Bina Ilmiah, 2024)
Welfare for teachers who teach in private vocational schools is different from teachers who are in public schools. This makes a difference in the psychological well-being of each teacher. Many factors can affect a person's psychological well-being, one of which is emotion focused- coping. The purpose of this study was to determine the relationship between emotion focused-coping and psychological well-being. The research method in this study is a qualitative method with a correlational research design. The research instrument used in this study was The Ways of Coping scale to measure emotion-focused coping variables and the psychological well-being scale to measure psychological well-being variables. The results of the correlation test using Pearson's correlation yielded a correlation coefficient of 0.009 with a significance of 0.947 (p <0.05). Based on these results it can be seen that the two variables have no relationship, so it can be concluded that emotion focused-coping has no effect on psychological well-being. It is possible that psychological well-being is influenced by factors other than emotion-focused coping